Evaluation of Self-Etching Adhesive and Er:YAG Laser Conditioning on the Shear Bond Strength of Orthodontic Brackets - Rosalía Contreras-Bulnes; Rogelio J. Scougall-Vilchis; Laura E. Rodríguez-Vilchis; Claudia Centeno-Pedraza; Oscar F. Olea-Mejía; María del Carmen Z. Alcántara-Galena (The Scientific World Journal)
The purpose of this study was to evaluate the shear bond strength, the adhesive remnant index scores, and etch surface of teeth prepared for orthodontic bracket bonding with self-etching primer and Er:YAG laser conditioning. One hundred and twenty bovine incisors were randomly divided into four groups. In Group I (Control), the teeth were conditioned with 35% phosphoric acid for 15 seconds. In Group II the teeth were conditioned with Transbond Plus SEP (5 sec); III and IV were irradiated with the Er:YAG 150 mJ (11.0 J/cm2), 150 mJ (19.1 J/cm2), respectively, at 7–12 Hz with water spray. After surface preparation, upper central incisor stainless steel brackets were bonded with Transbond Plus Color Change Adhesive. The teeth were stored in water at 37°C for 24 hours and shear bond strengths were measured, and adhesive remnant index (ARI) was determined. The conditioned surface was observed under a scanning electron microscope. One-way ANOVA and chi-square test were used. Group I showed the significantly highest values of bond strength with a mean value of 8.2 megapascals (MPa). The lesser amount of adhesive remnant was found in Group III. The results of this study suggest that Er:YAG laser irradiation could not be an option for enamel conditioning.